Malformations of the cerebral cortex and epilepsy. Clinical lecture - A. S. Kotov; K. V. Firsov (Русский журнал детской неврологии, 2022)
Malformations of the cerebral cortex are often the causes of epilepsy. The latest changes in their classification are summarized. The description of lissencephaly and Miller–Dicker syndrome, pachygyria, polymicrogyria, hemimegaloencephaly, holoprosencephaly, schizencephaly, gray matter heterotopia is given. The features of epilepsy in these diseases are described. Magnetic resonance imaging scans for focal cortical dysplasia, polymicrogyria, and gray matter heterotopia are presented.